(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In today’s world, the application available in the field of real time image processing are slow, provide results about a limited set of objects in a frame, and is not easily usable by people of all age groups. The nature of visual based knowledge is far better than anything else, if a person wishes to know about an object, or to remember an object, the best way is to first see how the object looks, and vice-versa, if you know how the object looks and feels, and you know what it is called, it would be best describable. Applications like Google lens are already prevalent in the market, but only available for android, which leaves rest of the OS users in vain, creating a market space for the untouched. Features like pose estimation can be inculcated through different software to yield AI based solutions to serve different purposes. Object detection and image classification can not only provide you information about the object, but in today’s connected world, can lead you to different sources of knowledge for the same, be it a link to buy the object, or a thesis about it or some facts about it.